Faithful renderings : Jewish-Christian difference and the politics of translation - Seidman, Naomi (Chicago : University of Chicago Press, 2006)
Faithful Renderings reads translation history through the lens of Jewish-Christian difference and, conversely, views Jewish-Christian difference as an effect of translation. Subjecting translation to a theological-political analysis, Seidman asks how the charged Jewish-Christian relationship--and more particularly the dependence of Christianity on the texts and translations of a rival religion--has haunted the theory and practice of translation in the West. Bringing together central issues in translation studies with episodes in Jewish-Christian history, Naomi Seidman considers a range of texts.
The translator as double agent -- Immaculate translation : sexual fidelity, textual transmission, and the virgin birth -- "The beauty of Greece in the tents of Shem" : Aquila between the camps -- False friends : conversion and translation from Jerome to Luther -- A translator culture -- The Holocaust in every tongue -- Translation and assimilation : Singer in America -- Endecktes Judenthum? : a translator's note.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Translating; Bible. -- Versions; Bible; Jews -- Languages -- Translating; Hebrew language -- Translating; Jewish literature -- Translations -- History and criticism; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Translating and interpreting -- Political aspects; LANGUAGE ARTS & DISCIPLINES -- Translating & Interpreting; Oude Testament; Vertalingen; Joden; Christenen; Christianity; Hebrew language -- Translating; Interfaith relations; Judaism; Translating and interpreting -- Political aspects; Electronic books; Criticism, interpretation, etc